Match factor extensions - Burt, C.; Caccetta, Louis (2018)
© 2018, Springer International Publishing AG. The match factor is defined as the ratio of truck arrival rate to loader service time. For the mining industry, this ratio is an important performance indicator with a dual purpose: during the equipment selection phase, it can be used to determine an appropriate fleet size such that the truck fleet productivity matches that of the loader fleet; during the operational phase, the match factor can be used to estimate the relative efficiency of the selected fleet. Prior to our work the match factor ratio has been restricted to homogeneous fleets. However, heterogeneous fleets are very common in large scale mines. In this chapter, we present a detailed account of the match factor ratio in mining and develop several extensions to the match factor ratio to allow for heterogeneous fleets.